Hydrochemistry, chemical weathering and their significance on carbon cycle in the Heilong (Amur) River Basin, Northeast China. (June 2023) - Zheng, Xu; Nel, Werner; Peng, Jingcheng; Wu, Weihua
Abstract: Chemical weathering is regarded as a "geological thermostat", affecting the global carbon cycle and long-term climate stability, and hydrochemistry of river is the important way to study weathering. The Heilong River (Amur River), as one of the largest rivers in the temperate/cool temperate zone, has received few studies on the chemical weathering rate and its contribution to the global carbon cycle in the entire Chinese section. This paper presents the hydrochemistry of river water, lake water, and groundwater from the arid upper reaches, the Greater Hinggan Mountains in the middle reaches, and the fluvial plain in the lower reaches of the Heilong River. TDS values range from 26.8 mg/l to 1141 mg/l with an average of 189 mg/l. The arid upper reaches are affected by strong evaporation and/or evaporite minerals dissolution, and the ion contents of some surface water and underground water exceed the quality standard for drinking water. Although the downstream flood plain area is highly industrial and agricultural, water chemistry shows that anthropogenic activities have not significantly deteriorated water quality. The chemical weathering rate of the small granitic and basaltic watersheds in the Heilong River Basin is within the lowest range in the world, which further demonstrates the control of climate factors on chemical weathering. The calculated CO2 consumption flux from silicate weathering in the Heilong River Basin is from 82.3 × 10 9 to 196 × 10 9  mol/y, accounting for 0.95%–2.25% of the global consumption values with a proportion of area of ∼1.2%. Compared with other temperate/cool temperate rivers worldwide, it is comparable to the Yenisei River in Siberia, but much higher than the Ob River and Lena River in Siberia, Mackenzie River and Yukon River in North America. Graphical abstract: Image 1 Highlights: The hydrochemistry in the arid upper reaches is strongly influenced by evaporation. The weathering rate of small silicate watersheds is in the global low range. The CO2 consumption in the Amur River is very prominent in cold temperate rivers.